Pemanfaatan Limbah Daun Jati Kering dan Serbuk Gergaji Kayu sebagai Bahan Baku Arang Briket di Desa Bubulan - Hery Indria Dwi Puspita; Gandu Eko Julianto Suyoso; Rudianto Rudianto; Andi Sanata; Ahmad Yasim (Indonesian Journal Publisher, 2024)
The Bubulan Village has rich natural resources, one of which is high-quality teak trees contributing to the productivity of teak trees in Bojonegoro Regency. Despite its advantages, teak trees in Bubulan Village hold the potential for economically valuable waste, namely teak leaf waste accumulating in the forest area. Additionally, Bubulan Village is home to wooden furniture craftsmen, and every production process generates wood sawdust waste.This community service aims to empower the people of Bubulan Village in managing this waste through training on the utilization of dried teak leaf waste and wood sawdust as raw materials for charcoal briquettes. The service method begins with partner surveys, followed by reference studies and a simulation of the charcoal-making process by the team. Subsequently, tools for making charcoal briquettes (including the creation of a charcoal stove) are procured. The activities continue with outreach to showcase the potential of Bubulan Village, followed by training on the utilization of teak leaf waste and wood sawdust as raw materials for charcoal briquettes.Representatives from the youth organization (karang taruna), village officials, and 20 residents of Bubulan Village attended this community service. The outcomes of this service include an increase in participants' knowledge about charcoal briquettes made from dried teak leaves and wood sawdust by 49%. The designed and made charcoal stove by the service team functions well. Briquettes made from dried teak leaves ignite more easily but have a shorter burning duration compared to briquettes made from wood sawdust. Further testing is needed to determine the calorific value, ash content, and moisture content of these briquettes, as well as additional tests on the efficiency of the charcoal stove.Written in English with a distance between sentences of 1 space and the number of words between 150-250. The abstract should contain introductions, methods, results and discussions and conclusions (without citation). Avoid using citations in the abstract.